Application of strategy planning for the teaching of forestry at university level - Chacon C., Iván; Neuenschwander A., Rodolfo (Bosque (Valdivia), 1988)
During the last few years strategic planning has had an increasing application in the management of different kinds of enterprises and institutions in the country. However this outlook has had a less frequent use at University Forestry Departments. The purpose of this paper is to show the applicability of strategic planning to these institutions by reviewing basic concepts, and by analyzing the actual conditions and some examples of its use at this level.